From Noise to Signal : The Successful Turnaround of Poverty Measurement in Colombia - Azevedo, João Pedro (World Bank, Washington, DC, 2013)
In the mid-2000s, poverty measurement in Colombia was at a standstill. A dated poverty measurement methodology was clashing with improvements in the national household survey system. As a result, official poverty rates showed volatile trends, and a weak communication strategy produced an unconvincing storyline, which further resulted in the rapid deterioration of indicator credibility. This happened during a period of high and sustained growth that also included a number of poverty reduction interventions, such as the flagship program familias en accion and the unidos strategy. The public debate on poverty lost focus and moved from substantial policy discussions to technical measurement methods.